How income and price changes affect the electricity demand? Evidence from Turkiye's residential sector - Kavaz, Ismail (Elsevier, 2025)
This study undertakes a comprehensive analysis of the income and price elasticities of residential electricity demand for Turkiye, spanning from 1980 to 2018. By employing the Structural Time Series Modelling method, the short- and long-run factors of income elasticities are found as 0.20 and 0.32, while the corresponding price parameters are determined as -0.08 for the short-term and -0.14 in the long-term, respectively. These elasticity estimations are crucial for informing policy-making processes, particularly in strategizing for the residential sector in Turkiye. The inelastic nature of these estimates, being less than 1, suggests that electricity constitutes a necessary commodity within the residential sector of Turkiye. It implies a limited sensitivity of consumers to fluctuations in price and income, indicating that changes in these factors do not significantly alter residential electricity demand in Turkiye. Additionally, this study extends its insights by providing forecasts for residential electricity demand. The projections indicate that by the year 2030, the electricity demand within Turkiye's residential sector is projected to range between 90 and 106 Terawatt-hours (TWh). This forecasted data serves as an essential tool for future planning and policy development in the context of residential electricity consumption.
Keywords: Elasticity estimates; Structural time series modelling approach; Residential electricity demand; Forecasting; Turkiye